SARS-CoV-2: pathogenesis, evolution and ongoing efforts in drug and vaccine development (African Journal of Biomedical Research, 2021)
The world is currently battling a pandemic disease that is spreading rapidly due to severe acute respiratory syndrome coronavirus 19 (SARS-CoV-2) that belongs to a family of coronaviruses. As per 20th December 2020, more than 77 million people have been infected with more than 1.7 million fatality cases reported worldwide. In response to this Pandemic, several efforts are being put in place to identify possible remedies, including therapeutic agents and against this virus. Currently, there is no approved vaccine or drugs against the virus, even though some countries such as Japan have approved the investigational drug Remdesivir as a coronavirus regimen. Other drugs such as chloroquine, which is widely used in treatment, remains controversial as there is no scientific evidence that establishes its effectiveness in the control of SARS-COV-2. This review constitutes a summary of SARS-COV-2 genomics and evolutionary relationship to other viruses, pathogenicity, transmission as well as efforts that have been made in the development of drugs and vaccines against this virus. We envisage that this review will provide an insightful and extensive coverage on the virus as well as support researchers in vaccine development and effective treatment protocol.
Keywords: Coronavirus; COVID-19; SARS-CoV-2; pandemic; acute pneumonia